5(5x-5)-3=x-6-2

Simple and best practice solution for 5(5x-5)-3=x-6-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(5x-5)-3=x-6-2 equation:


Simplifying
5(5x + -5) + -3 = x + -6 + -2

Reorder the terms:
5(-5 + 5x) + -3 = x + -6 + -2
(-5 * 5 + 5x * 5) + -3 = x + -6 + -2
(-25 + 25x) + -3 = x + -6 + -2

Reorder the terms:
-25 + -3 + 25x = x + -6 + -2

Combine like terms: -25 + -3 = -28
-28 + 25x = x + -6 + -2

Reorder the terms:
-28 + 25x = -6 + -2 + x

Combine like terms: -6 + -2 = -8
-28 + 25x = -8 + x

Solving
-28 + 25x = -8 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-28 + 25x + -1x = -8 + x + -1x

Combine like terms: 25x + -1x = 24x
-28 + 24x = -8 + x + -1x

Combine like terms: x + -1x = 0
-28 + 24x = -8 + 0
-28 + 24x = -8

Add '28' to each side of the equation.
-28 + 28 + 24x = -8 + 28

Combine like terms: -28 + 28 = 0
0 + 24x = -8 + 28
24x = -8 + 28

Combine like terms: -8 + 28 = 20
24x = 20

Divide each side by '24'.
x = 0.8333333333

Simplifying
x = 0.8333333333

See similar equations:

| 2x^2+2x-119=0 | | -8x+3x-7= | | C+ax=b-dx | | 6x+3=-37+2x | | 9x+8=68+3x | | B=-1+3a | | 2(x-5)-3(2t-7)=12-5(3t+1) | | 30-8x=15-5x | | 2u+4=u-7 | | 5+4(3c-1)= | | 2(5x+2)=3x-17 | | 4(3x-4)+8=4x+32 | | 22=2(2x-1) | | 2x+23=5x+35 | | 7x+20=76 | | -3x-5=2(x-5) | | .30+1.19=2.99 | | 3.00+8.0=6.75 | | 15x-2*(5x-3)=2*(x+9) | | 4(36-12h+h^2)-18+3h-(144-18)= | | -7+3x=-34 | | 28-3c=14 | | 5=6x-1 | | y=x^4+1x^2-30 | | P=20-5Q | | x^4+1x^2-30=0 | | (10x+9)=3 | | 3*5*6=153072 | | 5x-7=7x+6 | | 58=10x+8 | | 64x^4-27x=0 | | 11.5-8.5= |

Equations solver categories